Economical and Statistical Optimization of the Maintenance in the Production Process - Cézová, Eliška (Manufacturing Technology Journal, 2023)
The article presents a comprehensive example that demonstrates the control of a plastic injection process in practice. It includes measurement and analysis of the production process, its control using a control diagram to bring the production process to a state under statistical control by applying tests of non-random clusters and subsequent evaluation of process capability. The last part of the article gives an example of the maintenance of economical statistical optimization for four scenarios.
Keywords: Quality control; control chart; process capability; process control; injection moulding; plastic maintenance management; economic and statistical optimization; non-conforming process management